2009
DOI: 10.1515/cclm.2009.129
|View full text |Cite
|
Sign up to set email alerts
|

A routine method for the quantification of the novel antimycotic drug posaconazole in plasma using liquid chromatography-tandem mass spectrometry

Abstract: Background: Posaconazole is now widely used for prophylaxis of invasive fungal infections in immunocompromised patients. The pharmacokinetic properties of the drug argue for therapeutic monitoring, but so far described analytical methods have shortcomings with respect to application in a routine setting. The aim of our work was to develop an analytical method suitable for routine use. Methods: Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used. For sample preparation, protein precipitation foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Moreover, a mean deviation of approximately 50% in patient samples was found following comparative measurements during evaluation of a LC-MS/MS method adapted from Ref. (28). Inspection of the chromatograms showed that peak width was wider and peak shape was left side shifted.…”
Section: Identification Of Glucuronide Metabolitesmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, a mean deviation of approximately 50% in patient samples was found following comparative measurements during evaluation of a LC-MS/MS method adapted from Ref. (28). Inspection of the chromatograms showed that peak width was wider and peak shape was left side shifted.…”
Section: Identification Of Glucuronide Metabolitesmentioning
confidence: 95%
“…The method was performed essentially as described previously (28). It was comprised of a precipitation step, followed by online SPE and isocratic elution into the MS.…”
Section: Lc-ms/msmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique has been proved to be the most rapid and simplest procedure for sample preparation, and is widely accepted in many clinical and analytical laboratories. Quantitative extraction of posaconazole from human plasma or serum has been reported previously by using acetonitrile [22,26,29,31], methanol [23,31,33] or mixtures of both solvents [19][20][21]25] as the extracting reagent in sample preparation. The use of perchloric acid as a precipitating agent had also been previously examined by Zhang et al [31], and the addition of perchloric acid to methanol extraction proved to be advantageous.…”
Section: Solvent Extraction In a Single Dilution Stepmentioning
confidence: 99%
“…Therapeutic drug monitoring of a patient's serum or plasma has been a useful tool to detect drug exposures outside of the therapeutic window and to help individualize a dosage regimen and treatment, increasing therapeutic efficacy, and decreasing side effects . Reported methods for the analysis of posaconazole are mostly high-performance liquid chromatography (HPLC) with mass spectrometry [13][14][15][16][17][18][19][20][21][22][23][24][25], ultraviolet [26][27][28][29][30][31] and fluorescence [32][33][34][35] detections. Mass spectrometry (MS) and tandem mass spectrometry (MS/MS) are superior in sensitivity and specificity to ultraviolet (UV) and fluorescence (FL) detections.…”
Section: Introductionmentioning
confidence: 99%